Design of a Monitoring Device and System for Measuring Heart Rate, Oxygen Saturation and Body Temperature Based on the Internet of Things (IoT) - Hutahaean, Yoslina; Hapsari, Dini Shafira; Rusdiyanto, Dian (Jurnal Teknik Elektro Indonesia, 2025)
Medical technology have developed rapidly. This is conducted to support health services and prevent the worst conditions that can be experienced by someone who has health problems. This research proposes medical devices based on internet of things (IoT). The proposed device is an integrated system with sensors to detect body temperature, heart rate and oxygen saturation. The sensor reading results can be seen via the LCD and monitored via the website. Sensors and IoT systems use Arduino, where the sensors used are the MAX30100 sensor and the MLX90614 sensor. Meanwhile, the Wemos D1 mini is used to send sensor reading data to the website. To validate the performance of the tool, a comparison was carried out using an oximeter and a thermometer. The test results showed that the difference in oxygen saturation and body temperature readings was no more than 1%, while the difference in heart rate readings had an average difference of 1.13%. Monitoring on websites in real time is able to read sensor detections with a time lag from the tool to the website of around 5 seconds. The research results show that the design of the tool is in accordance with the desired specifications and can be applied in the health sector.